Current trends and research topics regarding liver 3D bioprinting: A bibliometric analysis research - Jin, Bao; Liu, Yitong; Du, Shunda; Sang, Xinting; Yang, Huayu; Mao, Yilei (Frontiers in Cell and Developmental Biology, 2022)
Introduction: Over recent years, 3D bioprinting has changed dramatically. The articles related to liver 3D bioprinting have not been quantitatively analyzed. In this article, we screen all articles related to liver 3D bioprinting until January 2022 and analyzed them using bibliometric citation analysis to characterize the current trends in liver 3D bioprinting. Methods: The articles were identified and analyzed from the Clarivate Analytics Web of Science Core Collection database. Results: Until 1 January 2022, 71 articles focusing on liver 3D bioprinting were identified. There was an increase in the number of articles in 2015. Most articles came from the USA (n=27), followed by South Korea (n=22), China (n=16), and Japan (n=5). The printing technology of liver 3D printing was the most studied topic (n=29). Biofabrication published the highest number of papers (n=16) with 1524 total citations. Conclusions: Based on bibliometric analysis of the articles until January 2022, a comprehensive analysis of the liver 3D bioprinting articles highlighted the current trends and research topics of this field. The data should provide clinicians and researchers insight into future directions relative to the liver 3D bioprinting.